The evolving management of the appendix mass in the era of laparoscopy and interventional radiology. Issue 2 (April 2017) - Forsyth, James; Lasithiotakis, Konstantinos; Peter, Mark
Abstract: Aim: An appendix mass is the result of a walled-off perforation of the appendix which localises, resulting in a mass and it is encountered in up to 7% of patients presenting with acute appendicitis. However, its management is controversial due to the lack of high level evidence. This review article sets out a rationale diagnostic and therapeutic strategy for the appendix mass based upon up-to-date available evidence. Methods: A literature review of the investigation and management of appendix mass/complicated appendicitis was undertaken using PubMed, EMBASE and Google Scholar. Results/conclusion: No prospective studies were identified. The great majority of recent evidence supports a conservative management approach avoiding urgent appendicectomy because of the high risk of major complications and bowel resection. Appendix abscesses over 5 cm in diameter and persistent abscesses should be drained percutaneously along with antibiotics. Appendix phlegmon should be treated with antibiotics alone. Surgery is reserved for patients who fail conservative treatment. Routine interval appendicectomy is not recommended, but should be considered in the context of persistent faecolith, ongoing right iliac fossa pain, recurrent appendicitis and appendix mass persistent beyond 2 weeks. Clinicians should be particularly wary of patients with appendix mass aged over 40 and those with features suggesting malignancy.